2008
DOI: 10.1002/hyp.7106
|View full text |Cite
|
Sign up to set email alerts
|

Floodplain stratigraphy of the ice jam dominated middle Yukon River: a new approach to long‐term flood frequency

Abstract: Abstract:Floodplain stratigraphy is used as a new method for reconstructing ice jam flood histories of northern rivers. The method, based on reconstruction of the sedimentary record of vertically-accreting floodplains, relies on stratigraphic logging and interpretation of floodplain sediments, which result from successive ice jam floods, and radiocarbon dating of inter-flood organic material for chronology. In a case study along a reach of the Yukon River that straddles the Yukon-Alaska border, the method is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…Floodplain sediments have been used extensively to reconstruct paleoflood frequency in a wide variety of physiographic and climatic settings (Brackenridge, 1981;1988;Kochel and Baker, 1982;1988;Baker et al, 1983;Ely and Baker, 1985), but only recently has the method been applied to ice-jam floods. Along the Yukon River Livingston et al (2009) showed that floodplain exposures containing repetitive overbank flood-deposited sediment layers separated by organic material can be used to reconstruct long-term ice-jam flood frequency. The sediment layers (flood beds) are slackwater deposits that accumulate on the floodplain surface during high magnitude ice-jam floods.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Floodplain sediments have been used extensively to reconstruct paleoflood frequency in a wide variety of physiographic and climatic settings (Brackenridge, 1981;1988;Kochel and Baker, 1982;1988;Baker et al, 1983;Ely and Baker, 1985), but only recently has the method been applied to ice-jam floods. Along the Yukon River Livingston et al (2009) showed that floodplain exposures containing repetitive overbank flood-deposited sediment layers separated by organic material can be used to reconstruct long-term ice-jam flood frequency. The sediment layers (flood beds) are slackwater deposits that accumulate on the floodplain surface during high magnitude ice-jam floods.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study Livingston et al (2009) used floodplain stratigraphy to reconstruct a 2000-year ice-jam flood history of a segment of the Yukon River straddling the Yukon-Alaska border. The method is based on the recognition of distinct, repetitive overbank flood-deposited sediment layers (beds) separated by organic material.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations